An online system for issuing buildings permits in light of e-government in Egypt. Issue 1 (31st December 2022) - Abdel Wahed, Mona Mahrous; Ismail, Tarek Saeed
ABSTRACT: A building permit is the green light in housing development projects, without the permit issued from the local authority, no construction can legally take place. The process of issuing buildings permits is complex and faces many problems and difficulties. The current permitting system in Egypt is a traditional manual system, resulting in a set of consequences such as loss of time, the possibility of human error, the possibility of losing permit papers, and other consequences. Therefore, the presence of an electronic online system capable of applying and submitting the permit requirements will be necessary to facilitate the work of the local authorities' employees, as well as to facilitate the process of obtaining building permits for the citizens. The electronic online permitting system speeds up the building permit process for individuals, contractors, employees, and plan reviewers. This system changes the way governments provide services to the community by speeding the process for the citizens and providing better and more timely information to the local authority's staff, decision-makers, and city officials. The objective of this paper is to develop a conceptual framework for an electronic online system for issuing building permits in the Egyptian context regarding its laws and regulations to support citizens and local authority's staff in issuing buildings permits. It also discusses the organizations involved in issuing buildings permits, their responsibilities and the requirements and data needed for the online system.